2016
DOI: 10.1063/1.4943112
|View full text |Cite
|
Sign up to set email alerts
|

Initial measurements of two- and three-dimensional ordering, waves, and plasma filamentation in the Magnetized Dusty Plasma Experiment

Abstract: The Magnetized Dusty Plasma Experiment at Auburn University has been operational for over one year. In that time, a number of experiments have been performed at magnetic fields up to B = 2.5 T to explore the interaction between magnetized plasmas and charged, micron-sized dust particles. This paper reports on the initial results from studies of: (a) the formation of imposed, ordered structures, (b) the properties of dust wave waves in a rotating frame, and (c) the generation of plasma filaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 65 publications
1
51
0
Order By: Relevance
“…Unlike the case of striation under identical conditions, the omega vector is directed opposite to the magnetic induction. The absolute value of the angular velocity is record‐breaking among all we know from the literature about structure rotation in strong magnetic fields …”
Section: Results and Discussion Of Fast Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the case of striation under identical conditions, the omega vector is directed opposite to the magnetic induction. The absolute value of the angular velocity is record‐breaking among all we know from the literature about structure rotation in strong magnetic fields …”
Section: Results and Discussion Of Fast Rotationmentioning
confidence: 99%
“…A number of studies have identified several physical phenomena associated with the dusty structures, their geometry, their dynamics in a magnetic field, and the ordering of particles. Nowadays, studies of dusty plasmas in magnetic fields continue, and the magnetic field magnitude range has been sufficiently widened . And the higher range of magnetic induction is a subject of certain interest of current research.…”
Section: Introductionmentioning
confidence: 99%
“…Today, there are several works in which the dusty plasma was studied in strong magnetic field. Since, where authors reported about instability of the dc discharge and its influence on dusty plasma, there was a number of works performed in the conditions of rf discharge in magnetic field up to 2 × 10 4 G . In recent work, it was succeeded to create the dusty plasma in the conditions of the stratified glow discharge in a whole diapason of moderate magnetic field in neon.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic field factor showed itself rather fruitful for research. Therefore, the range of applied magnetic field now migrates from a lower value region towards a higher one, and the experiments with magnetic field are carried out in all key discharge types.…”
Section: Introductionmentioning
confidence: 99%